2019
DOI: 10.1002/hed.25639
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant external beam radiotherapy for locally invasive papillary thyroid cancer

Abstract: Background The goal of this study was to assess the impact of adjuvant external beam radiotherapy (EBRT) on survival in patients with locally invasive papillary thyroid carcinoma. Methods Propensity score analysis was performed on 870 patients with surgically resected T4 papillary thyroid carcinoma, identified in the Surveillance, Epidemiology, and End Results Database between 1988 and 2013. Results EBRT was associated with worse overall survival (OS) (HR 1.60, 95% CI 1.18‐2.16) and disease‐specific survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Finally, the role of adjuvant cervical EBRT remains controversial [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Although this study includes the course of seven patients receiving adjuvant EBRT, only two (28.6%) of them took benefit of treatment in terms of cervical clearance of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the role of adjuvant cervical EBRT remains controversial [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Although this study includes the course of seven patients receiving adjuvant EBRT, only two (28.6%) of them took benefit of treatment in terms of cervical clearance of disease.…”
Section: Discussionmentioning
confidence: 99%
“…A 405-population-based study showed that, targeting well-differentiated thyroid cancers with pT4 stage, the 10- and 15-year OS rates were 85.7% and 77.1%, respectively, for the non-EBRT group and 67.5% and 57.0%, respectively, for the EBRT group (HR, 2.229; 95% CI 1.570–3.164; P < 0.0001) 19 . A study by Megwalu et al similarly confirmed that EBRT was associated with worse overall survival 20 . The reason for the difference in survival results may be related to the small sample size of previous studies, which was not sufficient to detect survival differences.…”
Section: Discussionmentioning
confidence: 83%
“…A 405-population-based study showed that, targeting well-differentiated thyroid cancers with pT4 stage, the 10-and 15-year OS rates were 85.7% and 77.1%, respectively, for the non-EBRT group and 67.5% and 57.0%, respectively, for the EBRT group (HR, 2.229; 95% CI, 1.570-3.164; P < 0.0001) [19]. A study by Megwalu et al similarly con rmed that EBRT was associated with worse overall survival [20]. The reason for the difference in survival results may be related to the small sample size of previous studies, which was not su cient to detect survival differences.…”
Section: Discussionmentioning
confidence: 92%